Generation of variational standard plant room solutions - Medjdoub, Benachir; Richens, Paul; Barnard, Nick (Automation in construction, 2003)
We have used the object-based CAD programming to take advantage of standardisation to handle the selection, sizing, layout and (potentially) pipe routing for Low-Pressure Hot Water (LPHW) plant rooms in buildings. Our approach combines automation and interactivity. From a simple specification of the plant room geometry (an orthogonal polygon with known obstructions, openings and external walls), and the heating load in kW, our software proceeds through a number of steps. First, the number and size of standard modular boilers, pumps, etc., are determined from the heat load. Then, a compatible optimising 3D variational solution is generated, using Constraint Logic Programming. To do this, we firstly enumerate a satisfactory topological solution, and then refine it to form a compatible geometrical solution. The final step generates pipe routes, using optimisation techniques to minimise the length of pipes and the number of bends. The solution obtained can be modified or improved by the designer, for which we have interactivity. Modifying the topology of the solution or the geometry of the plant room is done directly through the graphic interface, e.g. modifying a boiler position is done by dragging; the system automatically updates the 3D model including the pipe routing while maintaining all the design rules. The solutions generated by our prototype have been tested against conventional solutions in a benchmarking exercise. Advantages have been underlined and suggestions for further development have been made.